O papel da escola no contexto da esfera social : o ensaio para a vida pública - Petry, Clériston (2012)
This research discusses the school role in the social sphere context considering the inherent problem of dilution of the distinction between public and private in the modernity. According to Arendt the school is the institution between the private home domain and the world, therefore the issue of this work is the consolidation of the school role to do this transition. If the rise of the social sphere made the frontiers between the both spheres less clear, it is possible to discuss about the possibility of the school role be the same as the author presented in The crisis in education. The hypothesis is that the rise of the social sphere increased the authority and education crisis, due to this lack of frontiers between the two domains. On the other hand the school function would achieve the education to the citizenship, that is, the school would be the place where the students could rehearse to the public life, assuring the conservation of what is new on them, what makes possible the hope in the restore of public/politic life. The aim of this work is to research the implications of the rise to the school role, as well as the school challenges in the context described by Arendt. The methodology of this investigation is basically bibliographic. The main Arendt Works and the main commentators of the theme were analyzed. The work has three chapters, the first discusses about the rise of the social domain and the dilution of the distinction between public and private, the second chapter analyzes the end of authority in the modern society and its development contemporary, which is linked with the rise of the social sphere. Finally we present alternatives to discuss the school role as a domain of rehearse to the public life